Monthly Variations of the Winter Precipitation over the Philippines During the Mature Phase of Eastern Pacific El Niño - Liao, Wenxu; Fan, Yi; Zhu, Shoupeng; Huang, Yanyan; Lv, Yang (Frontiers in Earth Science, 2021)
The influence of ENSO events on winter precipitation anomalies in the Philippines has been well known since decades, but whether this effect is different between months needs further exploration. In this study, the monthly variations of precipitation over the Philippines in winter during the mature phases of ENSO events are investigated with datasets of reanalysis and observations from 1979 to 2019. Results indicate that only the eastern Pacific (EP) El Niño shows different influences on the Philippines winter precipitation among different months. In December during mature EP El Niño events, precipitation deficiency is not significant over the whole Philippines, whereas in January and February, precipitation decreases significantly over the southern Philippines as well as the areas to the southeast of the Philippines. Besides, the correlation between consecutive dry days over the southeast Philippines and ENSO is significantly positive in January and February but not in December. The eastward propagation of EP El Niño–related anomalous anticyclone over the western North Pacific (WNPAC) from December to February is proved responsible for the changed relationship between EP El Niño and precipitation. In December, the center of the WNPAC is located to the southeast of the Indo-China Peninsula, inducing weak lower-level wind anomalies and, consequently, weak vertical movement and water vapor transport anomalies over the Philippines, which exerts limited influence on the local precipitation. In January and February, by contrast, the center of WNPAC is located to the southeast of the Philippines, and therefore the southern Philippines is occupied by anticyclonic moisture transports and downward vertical motions, favoring less precipitations and larger than normal consecutive dry days over there.